2014
DOI: 10.22319/rmcp.v5i2.3220
|View full text |Cite
|
Sign up to set email alerts
|

Producción y calidad de forraje de variedades de avena en condiciones de temporal en Zacatecas, México

Abstract: Se evaluó la producción, calidad y componentes de rendimiento de seis variedades de avena forrajera en Zacatecas. Los experimentos se establecieron en julio de 2011 y 2012 en el municipio de Monte Escobedo. El diseño experimental fue bloques completos al azar con tres repeticiones, la densidad de siembra fue 120 kg ha-1 y dosis de fertilización de 60-40-00 de N, P2O5, K. La cosecha fue en estado fisiológico lechoso-masoso. En 2011 y 2012, La variedad Saía sobresalió (P<0.05) entre cultivares en rendimiento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
3
3
2
3
Order By: Relevance
“…The proportion of leaf 41% is higher to reports by Sánchez-Gutiérrez et al (2014) who reported at 106 d post sowing 24.2% of leaf, indicating a very mature black oat crop. A high proportion of leaf is an indicator of good quality of the grazed herbage since leaves are less lignified than stems.…”
Section: Black Oat and Pasture Variablescontrasting
confidence: 72%
See 3 more Smart Citations
“…The proportion of leaf 41% is higher to reports by Sánchez-Gutiérrez et al (2014) who reported at 106 d post sowing 24.2% of leaf, indicating a very mature black oat crop. A high proportion of leaf is an indicator of good quality of the grazed herbage since leaves are less lignified than stems.…”
Section: Black Oat and Pasture Variablescontrasting
confidence: 72%
“…These yields are higher than those reported by Ferolla et al (2007) in Brazil, who obtained 2317 and 1169 kg DM ha -1 under cutting and grazing, respectively. Yield for black oat in this work was also higher to reports by Sánchez-Gutiérrez et al (2014) in the north-central region of Mexico at first cut (4763 kg DM ha -1 ) at 106 d post sowing. Restelatto et al (2013) in Brazil evaluated the response of black oat to different fertilizer levels.…”
Section: Black Oat and Pasture Variablescontrasting
confidence: 42%
See 2 more Smart Citations
“…No existen reportes sobre los efectos del BC sobre dichas variables en avena forrajera. Sánchez-Gutiérrez et al (2014) mencionan que la etapa f isiológica al momento de la cosecha puede influir sobre NDT, ellos reportaron valores de hasta 56% cuando cosecharon avena de la variedad Karma en la etapa lechoso-masoso. Por lo tanto, podría deducirse que esos factores influyeron sobre los contenidos de NDT obtenidos en este estudio, los cuales, fueron más bajos, aunque aceptables para los animales.…”
Section: Resultados Y Discusiónunclassified